Ensuring skills are available in the right locations: are we there yet? A regional analysis of qualification gaps. Issue 8 (2nd August 2020) - Sevinc, Deniz; Green, Anne; Bryson, John R.; Collinson, Simon; Riley, Rebecca; Adderley, Simon
ABSTRACT: Matching skills supply and demand is critical for economic growth, competitiveness and inclusiveness. Yet, measuring skills is difficult. This paper develops an approach for measuring the gap between demand and supply of skills at the local level in the UK West Midlands region. It uses qualifications as a proxy for skills. By comparing the projected supply of qualifications with the forecast demand for qualifications from occupational forecasts, the analysis reveals significant skill mismatches with potential to constrain regional growth potential. Policy implications for connecting skills, transport and housing policy as part of local industrial strategies are explored.